A Note for Kalief: Unlocking Media Access to America’s Prisons - Patrick Huber (Washington University Journal of Law & Policy, 2017)
This Note discusses the current state of the first amendment with regard to access of the press to state prisons. Huber analyses the restrictions many prisons impose upon reporters in light of what happened to Kalief Browder, a boy confined for three years without a trial, who faced brutal violence by guards and two years of solitary confinement, in connection with stealing a backpack. The Article notes how journalistic efforts highlighted Browder’s mistreatment only after he tragically took his life. The author traces the current state of law governing media access to policies, including state-specific studies of current attempts to access prisons and failed legislative measures. The author concludes that these types of restrictions are unconstitutional, and proposes revised policies that would inform the public of the current state of U.S. prisons.
Keywords: First Amendment; Identity; Expression; Inmates; Study; Prisons